2017
DOI: 10.1039/c7cp05766k
|View full text |Cite
|
Sign up to set email alerts
|

Chromophores of chromophores: a bottom-up Hückel picture of the excited states of photoactive proteins

Abstract: Citation for published item:enst¤ oterD gte F nd henD ghrlie F nd erletD tn F F @PHIUA 9ghromophores of hromophores X ottomEup r¤ ukel piture of the exited sttes of phototive proteinsF9D hysil hemistry hemil physisFD IW @RRAF ppF PWUUPEPWUUWF Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 65 publications
12
49
0
Order By: Relevance
“…12 This previous study found that ezDyson predicted a smaller β 2 parameter (a more isotropic angular distribution) than was observed experimentally for the direct detachment feature at wavelengths longer than 370 nm. At wavelengths shorter than 370 nm, the overlapping feature arising from autodetachment from the S 1 state led to a decrease in the β 2 parameter, leading to values which appear more in agreement with ezDyson predictions at 12,[14][15][16][17] Good agreement was also found between the experimentally determined onset of the S 1 (1ππ * ) state (∼369 nm) and previous photoelectron spectroscopy measurements; 12 however, the higher resolution of the photoelectron spectra presented here has allowed us to locate a second bright resonance with AEE ∼ 335 nm. The experimentally determined average value of β 2 deviates from the trend predicted by ezDyson in the wavelength range where the direct detachment feature is overlapped in eKE with the resonant autodetachment feature, in agreement with the previous observations.…”
Section: Photoelectron Angular Distributionsmentioning
confidence: 78%
See 3 more Smart Citations
“…12 This previous study found that ezDyson predicted a smaller β 2 parameter (a more isotropic angular distribution) than was observed experimentally for the direct detachment feature at wavelengths longer than 370 nm. At wavelengths shorter than 370 nm, the overlapping feature arising from autodetachment from the S 1 state led to a decrease in the β 2 parameter, leading to values which appear more in agreement with ezDyson predictions at 12,[14][15][16][17] Good agreement was also found between the experimentally determined onset of the S 1 (1ππ * ) state (∼369 nm) and previous photoelectron spectroscopy measurements; 12 however, the higher resolution of the photoelectron spectra presented here has allowed us to locate a second bright resonance with AEE ∼ 335 nm. The experimentally determined average value of β 2 deviates from the trend predicted by ezDyson in the wavelength range where the direct detachment feature is overlapped in eKE with the resonant autodetachment feature, in agreement with the previous observations.…”
Section: Photoelectron Angular Distributionsmentioning
confidence: 78%
“…1, R=F and R=OMe, respectively) have been shown to become fluorescent when bound to specific ribonucleic acid (RNA) sequences. 9,10 It has been proposed that the electronic structure of the deprotonated GFP chromophore anion is governed by the phenolate molecular unit, 11,12 so our understanding of the electronic structure of the difluoro-and dimethoxy-substituted analogues will benefit from a detailed understanding of the electronic structure of the difluoroand dimethoxy-substituted phenolate building blocks. Experimentally, a direct way of probing the electronic structure of molecules is to use photoelectron spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The non-valence state of C6F6 − has the nuclear geometry of that of the S0 state owing to the very weak interaction of the diffuse orbital with the neutral core. 10,14 While there are clear signatures of dynamics involving resonances in the 2D-PE spectra (feature (iv) in Figure 1(a)), 22,[24][25][26] there is no apparent evidence for the formation of the non-valence state of C6F6 − . 14 This is of course not surprising given that the Franck-Condon overlap between anion and the neutral ground states is poor.…”
mentioning
confidence: 99%